2022
DOI: 10.1002/cbic.202200079
|View full text |Cite
|
Sign up to set email alerts
|

A Light‐Activatable Photocaged Variant of the Ultra‐High Affinity ALFA‐Tag Nanobody

Abstract: Nanobodies against short linear peptide‐epitopes are widely used to detect and bind proteins of interest (POI) in fusion constructs. Engineered nanobodies that can be controlled by light have found very recent attention for various extra‐ and intracellular applications. We here report the design of a photocaged variant of the ultra‐high affinity ALFA‐tag nanobody, also termed ALFA‐tag photobody. ortho‐Nitrobenzyl tyrosine was incorporated into the paratope region of the nanobody by genetic code expansion techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…First, NBY has been proposed as a universal proximal cage for the temporal blockage of protein activity (Wang et al, 2019;Wang et al, 2021). Second, NBY has been successfully employed to photocontrol antigen-antibody interactions (Bridge et al, 2019;Jedlitzke et al, 2019;Joest et al, 2021;Jedlitzke and Mootz, 2022;O'Shea et al, 2022;Yilmaz et al, 2022;Bridge et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…First, NBY has been proposed as a universal proximal cage for the temporal blockage of protein activity (Wang et al, 2019;Wang et al, 2021). Second, NBY has been successfully employed to photocontrol antigen-antibody interactions (Bridge et al, 2019;Jedlitzke et al, 2019;Joest et al, 2021;Jedlitzke and Mootz, 2022;O'Shea et al, 2022;Yilmaz et al, 2022;Bridge et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Alternatively, a collection of Nbs specifically raised against a prototypical, synthetic α-helical peptide (Alfa Tag) have been used for a variety of applications. 10,11 Nanobodies raised against the mammalian proteins α-synuclein, 12 β-catenin, 13 CXCR2 (refs 14, 15), and UBC6e 16 have been shown to bind to small peptide epitopes taken from these proteins. Previous work has shown that a nanobody (previously called VHH05 or VHH 6E , here named Nb 6E ) binds to a 14-mer peptide derived from the protein UBC6e (6E tag) with low nanomolar affinity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Efforts have been undertaken to identify Nbs that bind to peptide epitope tags . Nbs that bound to the human immunodeficiency virus protein gp41 were shown to bind to short peptide fragments of this protein, which could be applied as epitope tags (MoonTag, PepTag). , Alternatively, a collection of Nbs specifically raised against a prototypical, synthetic α-helical peptide (Alfa Tag) have been used for a variety of applications. , Nanobodies raised against the mammalian proteins α-synuclein, β-catenin, CXCR2 (refs , ), and UBC6e have been shown to bind to small peptide epitopes taken from these proteins. Previous work has shown that a nanobody (previously called VHH05 or VHH 6E , here named Nb 6E ) binds to a 14-mer peptide derived from the protein UBC6e (6E tag) with low nanomolar affinity .…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach suffers from low selectivity and versatility. These problems have been overcome by genetic code expansion, which uses the reprogramming of a stop codon to incorporate ncAAs at practically any desired position of a protein of interest. In this respect, photoxenoprotein engineering has enabled photocontrol of protein functions including modulation of enzyme activity and allostery, protein binding affinities, protein localization, and protein assembly and multimerization. …”
Section: Introductionmentioning
confidence: 99%